Carbon nanotube/silicon heterojunction solar cell with an active area of 4 cm2 realized using a multifunctional molybdenum oxide layer. (15th November 2021) - Huang, Xiaoxu; Hara, Emina; Sugime, Hisashi; Noda, Suguru
Abstract: Carbon nanotube (CNT)/silicon heterojunction solar cells have been extensively studied owing to the ease of junction fabrication. Encouraging power conversion efficiencies (PCEs) have been reported; however, many of them are limited to small cells (<1 cm 2 ). Herein, we report MoO x as a multifunctional layer that enables the size and performance enhancement. A 4 cm 2 -sized MoO x –CNT/n-Si solar cell with a PCE of 10.0% was realized via simple processes: dispersion–filtration–transfer for the CNT layer, hot-wire oxidation–sublimation deposition for the MoO x layer, mask-deposition for the Ag grid electrodes, and spin-coating for the polymethyl methacrylate anti-reflective layer. The MoO x layer played an essential role as a blocking layer to prevent direct contact and current leakage between Ag and n-Si while allowing the electrical conduction between Ag and CNT. It also served as a p-type dopant for the CNTs, which enhanced the electrical conduction and separation of electron–hole pairs at the heterojunction, and as an enhancer for the anti-reflective effect of the MoO x –CNT layer. Post-thermal annealing of MoO x was found to be crucially important, and the role of MoO x was also evaluated. This combination of a multifunctional MoO x layer with a metal grid electrode provides a facile route for practical CNT/Si heterojunction solar cells. Graphical abstract: Image 1